An updated meta-analysis of the asporin gene D-repeat in knee osteoarthritis: effects of gender and ethnicity - Liu, Ruoxi (J Orthop Surg Res, 2017)
BACKGROUND: Knee osteoarthritis (KOA) is the most prevalent form of knee joint disease and characterized by the progressive degeneration of articular cartilage. Although pathology of KOA remains unknown, genetic factors are considered to be the major cause. Asporin is a group of biologically active components of extracellular matrix (ECM) in articular cartilage, and asporin gene (ASPN) D-repeat polymorphism was reported to be associated with KOA. Thus, our meta-analysis is aimed at investigation of the association between asporin D-repeat polymorphism and susceptibility of KOA. METHODS: We gathered data from MEDLINE, Embase, OVID, and ScienceDirect to search relevant published epidemiological studies through April 2017. Compared with previous studies, our meta-analysis is the first study to investigate the association of ASPN D15, D16, and D17 alleles and KOA susceptibility by ethnic- and sex-stratified subgroup analysis. RESULTS: We found no significant association between D15 allele and susceptibility to KOA (OR = 1.05, 95% CI 0.95–1.17) in overall population. The same results were observed in the analysis of D16 (OR = 1.01, 95% CI 0.80–1.28) and D17 alleles (OR = 1.28, 95% CI 0.91–1.80). The ethnic- and sex-subgroup analyses did not alter the ORs. However, significant association was detected in the sensitivity analysis of D17 in overall population (OR = 1.05, 95% CI 0.95–1.17) and Asian population (OR = 1.78, 95% CI 1.02–3.11, P < 0.05). CONCLUSION: Our results indicated that D-repeat polymorphism of ASPN may not play a major role in susceptibility of KOA in ethnic- and sex-specific analysis. Because of the limitations of the present meta-analysis, firm conclusions could not be drawn based on the current evidence, and further studies are required to detect genuine role of ASPN.